Some reflections on „Rudiments and progress of clinical psychology” - Tylka, Jan (Studia Psychologica: Theoria et praxis, 2004)
This paper is devoted to roots of clinical psychology as well as current status of this specific discipline. The author presents some of philosophical suggestion and maximas, concerning mental growing and improving of individual person. As well we are dipping into works of such philosophers as Rochefaucauld, Nietzsche, we have to ascertain that they were great masters of spiritual life. Generally speaking current status of clinical psychology is diametrically opposed to their standing at the beginning of twenty century. The author gives a detailed description of procedure how to prepare oneself for an examination in order to be a specialist of clinical psychology.